Numerical prediction of curing and process-induced distortion of composite structures - Bernath, Alexander (Karlsruher Schriftenreihe Fahrzeugsystemtechnik, 2021)
Fiber-reinforced materials offer a huge potential for lightweight design of load-bearing structures. However, high-volume production of such parts is still a challenge in terms of cost efficiency and competitiveness. Numerical process simulation can be used to analyze underlying mechanisms and to find a suitable process design. In this study, the curing process of the resin is investigated with regard to its influence on RTM mold filling and process-induced distortion.